Histopathological Spectrum of Bladder Lesions : Our Observation in 128 Cystoscopic Specimen - Chowdhury, Md Babul Osman; Siddique, Md Saifuddin Ahmed; Islam, Md Mujahedul; Ahmed, ASM Mustaque (Journal of Chittagong Medical College Teachers' Association, 2017)
Background : Diseases of the bladder, particularly, inflammation (Cystitis), constitutes an important source of clinical signs & symptoms. Tumours of the bladder are an important source of both morbidity and mortality. The aim of the study was to make a histopathological evaluation of various bladder lesions and to observe the frequency of different bladder lesions. Material and methods : The study was conducted in the Department of Pathology, Chittagong Maa-O-Shishu Hospital Medical College (CMOSHMC) from Jan 2012 to Dec 2016. Patients particulars and histopathological diagnosis were kept in records. Tissue was processed in paraffin section technique and stained with routine Hematoxilin and eosin stains. Results : One hundred and twenty eight (128) cystoscopic sample were studied. Out of 128 cases males were 103 and 25 were females with a male to female ratio of 4.21:1. In malignant lesions the male to female ratio was 3.82:1. Age distribution ranges from 13 to 85 years with an average age of 57 years. The maximum age group belonged to 51 to 60 years and 61 to 70 years. The spectrum of lesions included non neoplastic and neoplastic lesions. Non neoplastic lesions were eosinophilic cystitis, granulomatous cystitis, radiation induced cystitis, chronic follicular cystitis and cystitis gladularis etc. The neoplastic lesions were, transitional cell papilloma, Papillary Urothelial Neoplasm of Low Malignant Potential (PUNLMP) low and high grade Transitional Cell Carcinoma (TCC) and leiomyosarcoma. Low grade TCC was the predominant type. Conclusion : Cystoscopic biopsy followed by histopatholigical examination is essential to diagnose any organic bladder lesion for proper management. Smooth muscle should be included in biopsy whenever malignancy is suspected. JCMCTA 2017 ; 28 (1) : 42 - 44